FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PELAKSANAAN PEMERIKSAAN ANC PADA IBU PRIMIGRAVIDA PADA ERA COVID-19 DI PUSKESMAS BTN ANTARA KOTA MAKASSAR - St. Aminah Ali; Baso Witman Adiaksa (Stikes Graha Edukasi Makassar, 2022)
Objective: to determine the factors related to the compliance with the implementation of the ANC examination on primigravida mothers during the covid-19 era at the Btn Antara Public Health Center Makassar City. Methods: This study uses an analytical survey method with a cross sectional approach where the researcher makes observations or measurements. The sample size in this study was 40 respondents with a total sampling technique. Data was collected using a questionnaire. Results: The results showed that there was a relationship between knowledge of ANC adherence of pregnant women with a P value = 0.039 which was smaller than the value = 0.05. There is a relationship between attitudes towards ANC compliance with the value of P = 0.002, which is smaller than the value of = 0.05. There is a relationship between husband's support for ANC compliance with a value of P=0.001 which is smaller than the value of =0.05. There is a relationship between knowledge, attitude, husband's support for ANC compliance. Conclusion: The conclusion in this study is that there is a relationship between knowledge, attitude, husband's support for ANC compliance. Suggestion: It is expected that health workers need to provide counseling or socialization about ANC (antenatal care).